IMPLEMENTASI PENGGUNAAN QRIS PADA SEKTOR UMKM DI KOTA SURABAYA - Alamsyah, Muhammad Aktoriel; Akbar, Jalaluddin Mohammad; Fajrin Naja, M. Afrirul; Kartini, Ida Ayu Nuh (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Digital payment transformation has become an essential strategy to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs). One of Indonesia’s key digital payment innovations is the Quick Response Code Indonesian Standard (QRIS), designed to standardize and simplify cashless transactions. This study aims to examine the implementation of QRIS among MSMEs in Surabaya City using a literature review method. Data were collected from scientific journal articles, Bank Indonesia reports, and relevant previous studies. The findings indicate that QRIS adoption among MSMEs in Surabaya has steadily increased, particularly in the culinary and retail sectors. The implementation of QRIS positively affects transaction efficiency, financial record management, and business professionalism. However, challenges remain, including limited digital literacy, security concerns, and resistance to shifting from cash-based transactions. Therefore, continuous policy support, education, and assistance are necessary to optimize QRIS utilization among MSMEs in a sustainable manner.